Factors associated with the symptoms onset and check up with testing for sexually transmitted infections among high school students in Serbia - Jelena Filimonovic; Milijana Relic; Goran Relic; Dragica Djoric; Jovana Pficer Kuzmanovic; Jelena Krdzic Milovanovic; Aleksandra Ilic; Zorica Sojevic Timotijevic; Srbislava Milinic; Marija Milic (Elsevier, 2024)
Background: Approximately 25% of the sexually active population is infected with sexually transmitted infections (STIs), among which adolescents are most often affected with a share of 50% among newly infected people. Methods: Cross-sectional study was conducted in three high schools in the city of Krusevac, Republic of Serbia, during 2021.The questionnaire collects data on the sociodemographic characteristics of students, their sexual activity and risky behavior, as well as data on knowledge about STIs and their occurrence. Results: Of the 778 students enrolled in the study, 140 (18.0%) reported having one or more symptoms of an STI, while 167 (21.5%) reported seeing a doctor for an examination or testing for a suspected STI.The most frequent visits to the doctor for check up and testing for STIs were due to suspicion of candida, condylomas and gonorrhea, and less frequently for HIV, herpes or syphilis.The results of the multinomial regression showed that attending medical school, worse grades in school, sexual intercourse after parties under the influence of alcohol and drugs, a greater number of sexual partners since the beginning of sexual activity, more frequent sexual intercourse on a monthly basis, not using contraceptive methods during sexual intercourse or use only combined oral pills were factors associated with the occurrence of STI symptoms in high school students in our study. Conclusion: It is evident that risky behaviors and non-use of prevention measures were factors associated with more frequent STI symptoms and medical check up.